Tunnel Collapse Mechanism and Its Control Strategy in Fault Fracture Zone - Jin Zhang; Mengxue Wang; Chuanhao Xi (Shock and Vibration)
Complex geological conditions such as fault fracture zone will have a significant adverse impact on tunnel engineering, and collapse, large deformation, and other problems are prominent. The research on the large deformation mechanism and control of tunnel crossing fault fracture zone can provide guidance for tunnel safety construction. Based on the Jingzhai tunnel, combined with geological analysis, theoretical research, numerical simulation, and other means, this paper studies and analyzes the large deformation mechanism of the tunnel. The control effect of different advanced reinforcement measures is studied.